Perancangan Panel Kontrol Mesin Penggiling Kelapa dengan SCADA - Noya, Donald Bastian; Putung, Yoice R.; Kasenda, Sonny; Sawidin, Sukandar (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2024)
Processing coconut into coconut milk is still done simply on a household scale in Indonesia. This method is considered impractical because it requires a lot of time and effort, especially when used in large quantities. To solve this problem, small and medium enterprises (SMEs) created a supervisory control and data acquisition (SCADA) system to control coconut grinding machines. The aim of this solution is to increase the productivity and efficiency of the coconut milk production process. The aim of this research is to create and implement a SCADA system that can monitor and control the operation of coconut grinding machines efficiently. System requirements analysis, SCADA architecture design, PLC (programmable logic control) programming, and user interface development are some of the research methods used. This research is expected to produce significant improvements in the performance and competitiveness of SMEs in the coconut processing industry